Regional Microstructural and Volumetric Magnetic Resonance Imaging (MRI) Abnormalities in the Corpus Callosum of Neonates With Congenital Heart Defect Undergoing Cardiac Surgery. (March 2016) - Hagmann, Cornelia; Singer, Jitka; Latal, Beatrice; Knirsch, Walter; Makki, Malek
The purpose of the study is to investigate the structural development of the corpus callosum in term neonates with congenital heart defect before and after surgery using diffusion tensor imaging and 3-dimensional T1-weighted magnetic resonance imaging (MRI). We compared parallel and radial diffusions, apparent diffusion coefficient (ADC), fractional anisotropy, and volume of 5 substructures of the corpus callosum: genu, rostral body, body, isthmus, and splenium. Compared to healthy controls, we found a significantly lower volume of the splenium and total corpus callosum and a higher radial diffusion and lower fractional anisotropy in the splenium of patients presurgery; a lower volume in all substructures in the postsurgery group; higher radial diffusion in the rostral body, body, and splenium; and a higher apparent diffusion coefficient in the splenium of postsurgery patients. Similar fractional anisotropy changes in congenital heart defect patients were reported in preterm infants. Our findings in apparent diffusion coefficient in the splenium of these patients (pre and postsurgery) are comparable to findings in preterm neonates with psychomotor delay. Delayed maturation of the isthmus was also reported in preterm infants.